Pharmacokinetics of Ciclopirox Olamine after Buccal Administration in Rabbits - Lukášová, Ivana; Muselík, Jan; Vetchý, David; Gajdziok, Jan; Gajdošová, Markéta; Juřica, Jan; Knotek, Zdeněk; Hauptman, Karel; Jekl, Vladimír (Current drug delivery, 2017)
BACKGROUND: Prevalence of oral mucosal fungal infections increases with the frequent administration of antibiotics, corticosteroids and immunosuppressive drugs. Therapeutically used antifungals are usually associated with a variety of drug interactions. Furthermore, there has been a noticeable increase in microorganisms resistant to these preparations. Mucoadhesive buccal films represent a modern therapeutic system for the treatment of oral mucosal fungal infection paired with a high degree of patient compliance. Ciclopirox olamine applied directly onto the oral mucosa offers an attractive alternative to treatment with systemic antifungals thanks to its low incidence of resistance and side effects. OBJECTIVE: The aim of this work was to evaluate the pharmacokinetic parameters of ciclopirox olamine after the buccal application of mucoadhesive film prepared by the solvent casting method. METHOD: A chromatographic method using an internal standard was developed and validated for evaluation of ciclopirox olamine plasma concentrations. Method accuracy was 88.5-104.6% and 89.5-99.7% for interday and intraday assays, respectively. RESULTS: The pharmacokinetic properties of ciclopirox olamine were studied in New Zealand White rabbits. The mucoadhesive films containing ciclopirox olamine in a total dose of 34.4 (33.0; 35.9) mg kg-1 were applied to all the rabbits. Plasma ciclopirox olamine concentrations were determined during the 12 h following application. The time taken to reach maximum plasma concentration was 1.7 (1.1; 2.2) h after the drug administration with cmax 5.73 (4.18; 7.28) μg mL-1. Overall elimination half-life was 3.8 (1.9; 10.8) h. CONCLUSION: The experiment suggests that oral mucoadhesive film may be a valuable alternative ciclopirox olamine administration.
Keywords: Pyridones; Administration, Buccal; Molecular Structure; pyridony; králíci; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Animals; mužské pohlaví; Male; aplikace bukální; Antifungal Agents; zvířata; Rabbits; antifungální látky; molekulární struktura